Oppbyggingen av en relasjonsbasert islandsk ordboksbase - Jónsson, Jón Hilmar (LexicoNordica, 2016)
The article describes the structuring of a relational dictionary database of Icelandic which partly derives from the lexicographic analysis of material in the Orðabók Háskólans archives and additionally builds upon the material of three related phraseological dictionaries of Icelandic from the years around 2000. The syntactic relations of words and phrases in this material reveal semantic relations building up a big collection of synonyms and other kinds of semantically related lexical items. An open and extendable lemma list (including multi-word lemmas) and a systematic presentation of the lemmas together with a comprehensive analysis of textual occurences bridges the gap between a corpus and a ready-made dictionary.